Bamba's cold & creamery business feasibility study using capital budgeting - Avian Dwi Putra (Indonesia Auditing Research Journal, 2021)
Basically, a business or project was born from an idea or ideas from business owners or managers. Idea or ideas can not be directly implemented in the form of investment. Investment to a business idea is done by sacrificing some money at the moment, so we need an assurance that these investments can provide benefits in the future. Therefore, a study needs to be done to assess the feasibility of a business idea. Business feasibility study aims to assess to what extent the feasibility of a business idea. Study the feasibility of the implementation of business ideas will minimize the risk faced by capital owners. Business feasibility study carried out in depth to obtain various information related to the respective business activities. Implementation of a business feasibility study covers several aspects related to business functions, namely the market and marketing aspects, technical aspects of production and technology, aspects of management and human resources, legal aspects, and financial and economic aspects. From several aspects, research and decision making focused on the financial aspects by utilizing the Net Present Value method, Internal Rate of Return method, Payback Period Method, and Profitability Index method. Based on those four methods calculations have been performed, the obtained results that Bamba's Cold & Creamery business idea is feasible for acceptance.